EXERCISE UNDER DEATH-ANXIETY: INVESTIGATING INDIVIDUAL EXERCISE PSYCHOLOGY AND BEHAVIOR FROM PERSPECTIVE OF TERROR MANAGEMENT AND BEHAVIORAL IMMUNE SYSTEM INTRODUCTION - Xuan Pan (Journal of Applied Sports Sciences)
The outbreak of COVID-19 has spread worldwide and become the world’s leading health concern. Individuals are advised to stay inside and do exercise at home to avoid exposure to the disease and their psychological state is concerned. This study aims to investigate physical exercise behavior and psychological states during COVID-19, and to provide helpful suggestions for making right policies or designing effective intervention programs to help the mass respond to the pandemic. Methods: we tested the hypotheses by conducting a national survey among 542 individuals, the data covered 28 provinces in China. Information about physical exercise habits, psychological states, perceived infection likelihood, perceived threat, attitudes towards exercise, and demographics was collected. A series of T-tests were applied to test the hypotheses. Results: The individuals who do exercise both before and during COVID-19 outbreak increased the physical exercise frequency and reduced the categories of physical activities during COVID-19. Individuals who perceive high-level threat increased future exercise time and consumption, whereas individuals surrounded by more confirmed cases (high-level objective threat) increased current exercise frequency and intensity. With the company of family members, individuals’ exercise intention, frequency, intensity and the possibility of future exercise time and activities was significantly higher. Conclusion: Under the threat of COVID-19, proximal defense (self-preservation) and distal defense (self-esteem enhancement) motivate individuals to increase exercise frequency. Individuals reduce types of physical activities and do exercise with family members to receive psychological security. Terror management theory and behavioral immune system provide theoretical explanations on individuals’ exercise behavior and psychology.